IJCM_344A: A Mixed-Methods Study On The Health Literacy Of School Teachers On The Mental Health Concerns, Coping Mechanisms, And Support Systems Of School- Age Adolescents In Puducherry India - Manjubairavi T.; Kumar Thiruselva D; Iswaryar (Wolters Kluwer Medknow Publications, 2024)
Background: The major challenges in addressing the adolescents with MHDs are lack of early identification, suitable interventions and treatment gap. Teachers are in the front lines of providing care, as students spend the majority of their early adolescence in school, where they endure social challenges. Objective: The study investigated teachers' mental health literacy and their capacity in assisting their students, in addition to current levels of knowledge, awareness, and comfort in addressing students' mental health concerns. Methodology: A Mixed Methods study with an Explanatory Sequential Design was conducted, among Puducherry's rural and urban schools using a validated questionnaire among students and in-depth interviews with teachers in instructional and further administrative roles, focus groups involving students and teachers separately to collect qualitative data. In SPSS 21, adjusted odds ratios (OR) for MHDs were computed using ordinal logistic regression. The qualitative data was analysed both deductively and inductively using NVivo 12. Results: One in ten demonstrated prosocial behaviours, while over half of them battled with peer, emotional, conduct, and hyperactivity issues. Thematic analysis linked MHDs primarily lack of domestic support, financial difficulties, close relationships, and bullying. Substance abuse and isolation were coping mechanisms, which had a negative effect on academic performance. Qualitatively, teachers reported feeling overburdened and stressed, because they lacked the comfort and knowledge to deal with students' mental health. Though most teachers believe there is a clear need for better mental health care in schools, many demonstrated a strong interest in professional development in this area. Conclusion: Restructuring the school health program promptly, adding mental health education to school curricula and creating surveillance data on adolescents' mental health are essential. We need school environments that are favourable of positive mental health because many MHD triggers happen there.